2019
DOI: 10.1016/j.scitotenv.2018.10.273
|View full text |Cite
|
Sign up to set email alerts
|

Limited reproductive impairment in a passerine bird species exposed along a perfluoroalkyl acid (PFAA) pollution gradient

Abstract: Although bird eggs have been used in biomonitoring studies on perfluoroalkyl acids (PFAAs), effects of environmental concentrations on reproduction remain largely unknown in wild birds. In the present study we examined the associations between the concentrations of 4 perfluoroalkyl sulfonic acids (PFSAs) and 11 perfluoroalkyl carboxylic acids (PFCAs) in the eggs of great tits (Parus major), collected along a distance gradient from a pollution source, and multiple reproductive parameters (including the start of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(81 citation statements)
references
References 70 publications
6
72
3
Order By: Relevance
“…No association was found between reproduction and total PFAS concentrations in eggs (Custer et al 2019; Figure 3) despite much higher exposure to total PFAS. This lack of an effect at very high PFAS concentrations was similar to a study of great tits in Belgium where there was only a slight reduction in hatching success in nests that hatched at least one egg (successful nests) at their site near a fluorochemical plant (Groffen et al 2019). Perfluorooctane sulfonate exposure in that study was 50 times higher in eggs at the site nearest the plant (34 251 ng/g wet wt) than present at Wurtsmith, the site with the highest known exposure in North America (Custer et al 2019).…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…No association was found between reproduction and total PFAS concentrations in eggs (Custer et al 2019; Figure 3) despite much higher exposure to total PFAS. This lack of an effect at very high PFAS concentrations was similar to a study of great tits in Belgium where there was only a slight reduction in hatching success in nests that hatched at least one egg (successful nests) at their site near a fluorochemical plant (Groffen et al 2019). Perfluorooctane sulfonate exposure in that study was 50 times higher in eggs at the site nearest the plant (34 251 ng/g wet wt) than present at Wurtsmith, the site with the highest known exposure in North America (Custer et al 2019).…”
Section: Introductionsupporting
confidence: 84%
“…Although many studies document exposure to PFASs in birds (see review in Ankley et al 2021), there are still relatively few field, or even laboratory, studies on PFAS reproductive effects when compared to other contaminants, such as polychlorinated biphenyls (PCBs), mercury (Hg), and p,p ‐DDE. Field reproductive effect studies on PFASs include studies on tree swallows ( Tachycineta bicolor ; Custer et al 2012, 2014, 2017, 2018, 2019), black‐legged kittiwakes ( Rissa tridactyla ; Tartu et al 2014), great tits ( Parus major ; Groffen et al 2019), and lesser black‐backed gulls ( Larus fuscus ; Bustnes et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One key challenge in conducting field studies lies in endpoint selection. Endpoints reported from studies on avian species have covered a range from suborganismal responses, including biomarkers and measures of oxidative stress (e.g., Blévin et al 2017a, 2017b; Lopez‐Antia et al 2017, 2019), to effects related to reproductive success such as eggshell thinning (Miljeteig et al 2012) and hatching success (e.g., Tartu et al 2014; Custer et al 2019; Groffen et al 2019). The avian studies that have included measures of reproductive success are especially valuable given the clear link between reproduction and potential population‐level impacts.…”
Section: Current Knowledge About Ecological Effects Of Pfasmentioning
confidence: 99%
“…64 In great tits (Parus major), high concentrations of PFAS interfered with reproduction success, by failure in hatching in particular. 65,66 Conversely, some studies found no consequences of PFAS concentrations on wild birds.…”
Section: Descriptive Statistics: Pfas Exposurementioning
confidence: 99%